O cinema documentário de Miguel Mirra e o movimento de documentaristas: o cinema junto aos oprimidos - Pacheco, Luis Jorge Orcasitas (Universidade Federal de São Carlos, 2018)
The present work is an approach to the trajectory and documentary work of Miguel Mirra, Argentine filmmaker who has developed several works in the field of communication and audiovisual production, motivated by the action of social movements that have been formed in his country during the last three decades. In this context, it is proposed to investigate and analyze the methods, concepts and ways in which this director structures a type of social and political documentary film, whose objective is to make visible and be in solidarity with the oppressed, the excluded and the exploited peoples. Based on a referential framework with historical, political, economic, argumentative and stylistic components, the project provides a reflective analytical of the cinematographic, cultural and ideological proposals of Miguel Mirra, whose documentary film is an immediate reflection of the cinematographic movements that emerged in Argentina. From the second half of the twentieth century, they have aimed to project a distinctive point of view, in order to generate alternative visions and new spheres of the public.

El presente trabajo es un acercamiento a la trayectoria y obra documental de Miguel Mirra, cineasta argentino que ha desarrollado diversos trabajos en el terreno de la comunicación y la producción audiovisual, motivados por la acción de los movimientos sociales que se han formado en su país durante las últimas tres décadas. En este contexto, se plantea indagar y analizar los métodos, los conceptos y las formas en que este realizador estructura un tipo de cine documental social y político, cuyo objetivo es visibilizar y ser solidario con los oprimidos, los excluidos y los pueblos explotados. A partir de un marco referencial con componentes históricos, políticos, económicos, argumentativos y estilísticos, el proyecto propende una reflexivo analítica de las propuestas cinematográficas, culturales e ideológicas de Miguel Mirra, cuyo cine documental es reflejo inmediato de los movimientos cinematográficos surgidos en Argentina a partir de la segunda mitad del siglo XX, que lo han encaminado a proyectar un punto de vista distintivo, para así generar visiones alternativas y nuevas esferas de lo público.
El cine documental de Miguel Mirra y el movimiento de documentalistas: el cine junto a los oprimidos
Keywords: Documentário social; Documentário político; Movimentos sociais; Oprimidos; Social documentary; Political documentary; Social movements; Opressed; Documental social; Documental político; Movimientos sociales; Oprimidos; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA